Cracking of silty mudstone subjected to wetting-drying cycles - Xiaowei Yu; Hongyuan Fu; Ling Zeng; Guijin Zhang; Hongri Zhang; Jie Liu (Journal of Rock Mechanics and Geotechnical Engineering, 2025)
Cracking affected by wetting-drying cycles is a major cause of shallow failure of soft rock slopes. Knowledge of rock tensile properties and cracking behaviors helps better assess the stability of soft rock slopes. This study aims to examine the cracking behaviors and tensile strength of silty mudstone under wetting-drying cycles. The wetting-drying cycle and Brazilian splitting tests were performed on silty mudstone considering various cycle number and amplitude. The cracking behaviors of wetting-drying cycles were analyzed by digital image correlation, three-dimensional (3D) scanning technology, and scanning electron microscopy. The results reveal a spiral-like pattern of crack ratio escalation in silty mudstone, with a higher crack ratio observed during drying than wetting. Tensile strength and fracture energy correlate negatively with cycle number or amplitude, with cycle number exerting a more pronounced effect. The variance of the maximum principal strain reflects stages of initial deformation, linear deformation, strain localization, and stable deformation. The formation of strain localization zones reveals the physical process of crack propagation. Crack tip opening displacement progresses through stages of slow growth, exponential growth, and linear growth, delineating the process from crack initiation to stable extension. Failure modes of silty mudstone primarily involve tensile and tensile-shear failure, influenced by the geometric parameters of cracks induced by wetting-drying cycles. Fracture surface roughness and fractal dimension increase with cycle number due to mineral dissolution, physical erosion, and nondirectional crack propagation. Hydration-swelling and dehydration-shrinkage of clay minerals, along with absorption-drying cracking, initiate and merge cracks, leading to degradation of the rock mechanical properties. The findings could provide insights for mitigating shallow cracking of soft rock slopes under wetting-drying cycles.